Effects of Postgraduate Education on Nursing and Reflections in the Clinic Field : A Qualitative Research (International Journal of Nursing Education, 2024)
Background: Nurses improve themselves with various trainings according to the developing era and patient needs. Determining the effects of postgraduate education in the clinical field opens new horizons for improving the quality of patient care.Aim: To determine the opinions of the participants about the effects of postgraduate education in nursing and the reflection of these effects on the clinic field and patient care by the nurse specialist.Methods: This is a phenomenological descriptive qualitative study which was data gathered through in-depth interviews with nurses, physicians, and patients. For content analysis, the data were subjected to thematic analysis.Results: The data obtained from the views of the participants about the effects of postgraduate education in nursing and its reflections on the clinic were combined under 4 main themes and 20 sub-codes.Conclusions: It was concluded that postgraduate education has effects on nursing roles, individual development, other professional development, increasing its professional value and scientific power, and these effects are reflected positively in clinical field.